INFECTION IN ELDERLY PATIENTS HOSPITALIZED IN A PRIVATE INSTITUTION IN NATAL/RN (Fiep Bulletin - online, 2014)
Descriptive and retrospective Study that aimed to characterize the occurrence of hospital infection (HI) in 65 elderly patients of a private hospital in Natal / RN. After institutional consent, the data were collected in the National Information System for Infection Control in Health Services (SINAIS) of the Commission of Hospital Infection Control. The variables collected had been: age, sex, length of stay in the institution, status of patients admitted, internship sector, basis disease, central venous catheter (CVC) use, site of hospital infection, hospital infection rate and antimicrobials use. The data were organized in Microsoft Excel software and transported to the SPSS 14.0 program for descriptive and inferential analysis. It was a prevalence of infection in the elderly aged between 70-79 years (40,0%) and male (53.8%). The most frequent basis diseases were the respiratory and cardiac failure, with 16.9% each. The most acquired hospital infections were: in the urinary tract (33.0%), in the bloodstream (32.1%), while 66.6% of them were related to CVC and pneumonia (16.5%). As to the clinical evolution, 60,0% of the patients had hospital discharge, 38.5% died and 1.5% remained hospitalized. The results show that elderly patients are more susceptible to hospital infections for longer remain hospitalized and are more exposed to invasive procedures and use of antimicrobials, hindering a faster cure and extending the length of hospitalization.
Keywords: Hospital infection; Elderly